Temperature-dependent burst failure of polymeric hollow fibers used in heat exchangers. (January 2022) - Bulejko, Pavel; Bartuli, Erik; Kůdelová, Tereza; Vančura, Jan
Highlights: Hollow fibers made of five polyamides and polyphenylene sulfide were tested. Burst pressure measured at temperature range of −40 to 160 °C. The results were analyzed using theoretical models. Burst pressures were in the range of 30 to 120 bar. Abstract: This work analyzes resistance of polyamide hollow fibers used for heat exchangers against extremely high pressures. Hollow fibers made of five different commercially available polyamides and one type of polyphenylene sulfide were tested at different temperatures ranging from −40 to 160 °C. After getting the fiber to the required temperature, pressure from a nitrogen vessel was gradually applied to the lumen side of a fiber until the fiber rupture. The results obtained for different polymers were then analyzed using various burst pressure models used to predict pressure durability of pipelines. The result showed decreasing burst pressure of polyamide fibers mostly from 100 bars to about 50 bars with increasing temperature from −40 to 160 °C. This was contrary to polyphenylene sulfide, which increased from 30 to about 60 bars in the same temperature range. The theoretical models were in a strong disagreement with experimental data and the results fluctuated significantly. However, the fibers showed outstanding durability against rupture no matter of the temperature, since the lowest burst pressure was about 40 bars at 160 °C. From the point of view of practical usability of polymeric hollow-fiber heat exchangers in automotive, the results indicate the polymeric fibers are able to operate at a wide range of conditions characterized by extreme temperature and pressure fluctuations typical for a car radiator.